Education and Services on Long-Term Contraceptive Methods in Taba Baru Village, Lubuklinggau Utara I Subdistrict - Fitria Apriani; Rustandi , Handi; Juwairah , Nur Falakh; Asmaja , Reni; Sari, Devi Rakin (Universitas Dehasen Bengkulu, 2025)
Family Planning (KB) is a strategic program in an effort to reduce birth rates and improve the quality of family life. One effective method is the Long-Term Contraceptive Method (MKJP), which includes IUD, implant, MOW, and MOP. In Lubuklinggau City, South Sumatra Province, the Percentage of MKJP KB Use is only 32%, especially in the Taba Baru Village area, only 10 people use MKJP KB from the target of 310 PUS. The Thematic Real Work Lecture Program (KKN-T) of Dehasen University Bengkulu in 2025 focuses on promotional efforts through an educational approach, namely with the MKJP KB Counseling method, distribution of leaflets and Digital education and Free KB Services. This activity is carried out through collaboration with village officials, the Lubuklinggau Utara I District KB Center and the local community. This study aims to evaluate the impact of free MKJP KB education and services on increasing awareness and participation of acceptors in Taba Baru Village. Activities are carried out through an educational approach and direct services. The results show an increase in public knowledge and interest in MKJP. Education has been proven to be effective as a promotional strategy in forming positive attitudes and increasing acceptor participation. Cross-sector collaboration and ongoing education are essential to support efforts to increase public awareness and participation in the use of MKJP KB.